Innovation of Potato Flour Based Soft Cookies with Red Kidney Bean Flour Subtitution: Hedonic, Physical, and Properties - Dian Rose Mahersi; Pudji Astuti (Universitas Negeri Padang, 2026)
The effect of red kidney bean flour substitution on the hedonic preference, physical, and chemical characteristics of potato flour-based soft cookies was investigated using an experimental method with Completely Randomized Design (CRD) consisting of one factor and four treatments, namely F0 (100% potato flour), F1 (70% potato flour : 30% red kidney bean flour), F2 (60% potato flour : 40% red kidney bean flour), and F3 (50% potato flour : 50% red kidney bean flour) with two replications. The mean values of the hedonic preference test were analyzed using the Kruskal-Wallis test, which showed that all parameters were significantly different with a significance value of 0,01 lower than 0,05 (p<0,05),therefore followed by the Mann-Whitney test.. The result showed that the substitution of red bean flour affected the characteristics of soft cookies. Treatmant F2 (60% potato flour : 40% red kidney bean flour) showed better panelist acceptance compared to the other treatments. Higher substitution levels of red bean flour tended to produce darker-colored soft cookies with a denser texture. The protein content of treatment F2 was 7.05%, while the moisture content of treatment F3 was 11.76%. all treatments met the minimum protein requirement of SNI 2973:2022 ≥5%, while moisture content in all treatments ecceeded the maximum permitted level (≤5%). Based on hedonic preference, physical, and chemical characteristic, treatment F2 (60% potato flour : 40% red kidney bean flour) demonstrated better result compared to the other treatments.